HUBUNGAN PENGETAHUAN DAN PERILAKU MASYARAKAT DI KOMPLEK PERTANIAN ATSIRI PERMAI RT 11 TERHADAP PENGGUNAAN OBAT HERBAL UNTUK SWAMEDIKASI SAKIT KEPALA PERIODE AGUSTUS – DESEMBER 2024: The Relationship of Knowledge and Behavior to the Use of Herbal Medicines for Self-Medication for Headaches for the Period August – December 2024 - Sri Cahyanti; Aprilia Fatma Elly; Linda Suryanti (UIMA Press, 2025)
This study aims to investigate the relationship between the level of knowledge and community behavior regarding the use of herbal medicines for self-medication of headaches in RT 11 Permai Essential Agricultural Complex, Bogor Regency, West Java. This type of research was an analytical study with a cross-sectional design to determine the relationship between the level of knowledge and behavior of self-medication (self-medication) analgesic headache in the community at the Permai Essential Agricultural Complex RT 11, Bogor Regency, West Java. Based on the results of the study, the knowledge and behavior questionnaire instrument was declared valid and reliable, making it the right measurement tool for this study. The univariate analysis revealed that the majority of respondents (59.3%) had a low level of knowledge about self-medication for headaches, although the majority (52.3%) exhibited appropriate self-medication behavior. In addition, the practice of using self-medication drugs was quite dominant among respondents (60.5%). Furthermore, bivariate analysis revealed a significant relationship between knowledge (p-value = 0.043) and behavior (p-value = 0.000) of the community with the use of herbal medicines for self-medication for headaches. This shows that good knowledge correlates with more appropriate self-medication behavior.